2008
DOI: 10.1152/ajpheart.00471.2008
|View full text |Cite
|
Sign up to set email alerts
|

Reverse changes in cardiac substrate oxidation in dogs recovering from heart failure

Abstract: Recchia FA. Reverse changes in cardiac substrate oxidation in dogs recovering from heart failure. Am J Physiol Heart Circ Physiol 295: H2098 -H2105, 2008. First published September 26, 2008 doi:10.1152/ajpheart.00471.2008.-When recovering from heart failure (HF), the myocardium displays a marked plasticity and can regain normal gene expression and function; however, recovery of substrate oxidation capacity has not been explored. We tested whether cardiac functional recovery is matched by normalization of ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 32 publications
4
31
0
Order By: Relevance
“…Therefore, we used a model that maintains LV dysfunction at stimulation rates that are closer to normal ranges for conscious dogs and that induced a progressive development of HF. In addition, we previously demonstrated that 16 wk of RV tachypacing induced irreversible systolic dysfunction (up to 7 wk after termination of pacing), which is in contrast with previous reports of canine tachypacing models (23,30). Further experiments are required to determine the effect of the duration of HF on the regulation of myocardial glucose transport.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Therefore, we used a model that maintains LV dysfunction at stimulation rates that are closer to normal ranges for conscious dogs and that induced a progressive development of HF. In addition, we previously demonstrated that 16 wk of RV tachypacing induced irreversible systolic dysfunction (up to 7 wk after termination of pacing), which is in contrast with previous reports of canine tachypacing models (23,30). Further experiments are required to determine the effect of the duration of HF on the regulation of myocardial glucose transport.…”
Section: Discussionmentioning
confidence: 64%
“…emic dilated cardiomyopathy, a switch of substrate selection toward glucose oxidation remains controversial, as several studies reported increased, unchanged, or decreased glucose uptake in the failing heart (12,13,16,17,20,23,26,31). In particular, there is recent evidence suggesting that chronic HF may promote metabolic changes, such as insulin resistance resulting in decreased glucose uptake and utilization (1,17,37).…”
mentioning
confidence: 99%
“…The decrease in aconitase was independent of a decrease in protein content, indicating that regulation of aconitase in hypoxia was likely via post-translational regulation. Downregulation of aconitase activity has also been identified in heart failure, suggesting a common signalling pathway (potentially via HIF) or conserved enzyme target [41]. In certain cell lines and genetic models, changes in aconitase have been linked to upstream changes in the iron-sulphur cluster assembly protein ISCU and frataxin [6,14,36].…”
Section: Discussionmentioning
confidence: 99%
“…Beagle dogs of either sex ranging from 3 to 14.3 yr of age (n ϭ 41) were maintained and studied in accordance with the National Institutes of Health Guide for Care and Use of Laboratory Animals; animal experiments were approved by the local animal care committee (Institutional Animal Care and Use Committee at New York Medical College, Albert Einstein College of Medicine, and Lovelace Respiratory Research Institute). Fifteen beagle dogs were chronically instrumented for evaluation of cardiac function, as previ-ously described (30,33,56). Cardiomyocytes obtained from male hound type dogs 7-9 mo old (n ϭ 4) were employed to test the rate dependency of the late Na ϩ current (INaL) by patch-clamp technique in voltage-clamp mode.…”
Section: Methodsmentioning
confidence: 99%